Taekwondo: Anthropometric characteristics and biomechanical advantage - Scamardella, F.; Limone, P.; Peluso Cassese, F.; Amato, G.; Latino, F.; Tafuri, F. (Journal of Physical Education and Sport, 2025)
Purpose. Taekwondo, the official Olympic sport since the Sydney 2000 Games, known for the emphasis placed by practitioners on football techniques, owes its diffusion to the continuous changes in the competition regulations characterized by the protection of the safety of competitors and the objective search for the assignment of scores. These variations and modifications of the regulations have changed over time the entire performance model and, consequently, the morphology of the typical athlete for combat. Methods. The research was conducted through the collection and statistics of the heights of athletes who took part in and reached the medal zone at the Tokyo 2020 and Paris 2024 Olympics. All 32 athletes who arrived on the Olympic podium were taken into consideration, all aged between 18 and 35, divided into 16 males and 16 females, in the eight 8 Olympic weight categories. The working hypothesis was to verify that the average height of the medal athletes has been increasing, comparing these data with the average heights of previous Olympic editions, favoring the biomechanical advantage dictated by longer lower levers (greater length). Results. The trends obtained from the comparison of average heights, both in the male and female fields, confirm with a good approximation that the average heights of athletes have increased, then stabilized in some cases. Conclusions. This study confirms the hypothesis that, in most weight categories, the average height of Olympic Taekwondo medalists has been increasing over time, aligning with the biomechanical advantages associated with longer lower limbs. However, in some categories, particularly the -58 kg and +80 kg men`s divisions and the +67 kg women`s category, height trends appear to have stabilized, suggesting the establishment of an optimal range for performance.